Functional assessment of myocardial ischaemia by intracoronary ECG - Christian Seiler; Marius Reto Bigler; Michael Stoller; Fabien Praz; George C M Siontis; Raphael Grossenbacher; Christine Tschannen (Open Heart)
Introduction In patients with chronic coronary syndrome, percutaneous coronary intervention targets haemodynamically significant stenoses, that is, those thought to cause ischaemia. Intracoronary ECG (icECG) detects ischaemia directly where it occurs. Thus, the goal of this study was to test the accuracy of icECG during pharmacological inotropic stress to determine functional coronary lesion severity in comparison to the structural parameter of quantitative angiographic per cent diameter stenosis (%S), as well as to the haemodynamic indices of fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR).Method The primary study endpoint of this prospective trial was the maximal change in icECG ST-segment shift during pharmacological inotropic stress induced by dobutamine plus atropine obtained within 1 min after reaching maximal heart rate(=220 - age). IcECG was acquired by attaching an alligator clamp to the angioplasty guidewire positioned downstream of the stenosis. For the pressure-derived stenosis severity ratios, coronary perfusion pressure and simultaneous aortic pressure were continuously recorded.Results There was a direct linear relation between icECG ST-segment shift and %S: icECG=−0.8+0.03*%S (r2=0.164; p<0.0001). There were inverse linear correlations between FFR and %S: FFR=1.1–6.1*10–3*%S (r2=0.494; p<0.0001), and between iFR and %S: iFR=1.27–8.6*10–3*%S (r2=0.461; p<0.0001). Using a %S-threshold of ≥50% as the reference for structural stenosis relevance, receiver operating characteristics-analysis of absolute icECG ST-segment shift during hyperemia showed an area under the curve (AUC) of 0.678±0.054 (p=0.002; sensitivity=85%, specificity=50% at 0.34 mV). AUC for FFR was 0.854±0.037 (p<0.0001; sensitivity=64%, specificity=96% at 0.78), and for iFR it was 0.816±0.043 (p<0.0001;sensitivity=62%, specificity=96% at 0.83).Conclusions Hyperaemic icECG ST-segment shift detects structurally relevant coronary stenotic lesions with high sensitivity, while they are identified highly specific by FFR and iFR.